Review paper Rupatadine: a novel second-generation antihistamine - Grzelewska-Rzymowska, Iwona; Górski, Paweł (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Histamine is the primary mediator involved in the pathogenesis of allergic rhinitis and chronic idiopathic urticaria. Platelet-activating factor (PAF) is also a mediator which plays a key role in the allergic reaction. Rupatadine is a novel antihistamine of the second generation approved recently in Europe for the treatment of allergic rhinitis and chronic idiopathic urticaria in patients aged ≥ 12 years. Rupatadine shows both antihistamine and anti-PAF effects because it presents hybrid molecule. One unit of this molecule has high affinity to H1 receptor, and the second one blocks the receptor for PAF. Relative potency of rupatadine is much higher than that of other second generation antihistamines. Rupatadine also has anti-allergic and anti-inflammatory activity. The drug blocked the release of histamine from mast cells and other proinflammatory cytokines such as IL-5, IL-6, IL-8, TNF-α and GM-CSF from activating human lymphocytes. It also blocked in vitro chemotaxis of human eosinophils to eotaxin, and neutrophils to PAF and LTB 4 . Anti-allergic and anti-inflammatory activity of rupatadine results from blocking NFκβ. Clinical trials have indicated that rupatadine is significantly more effective than placebo and equally effective as other antihistamines of the second generation. Rupatadine is well tolerated, and side effects are mild and moderate, the most common ones were headache and somnolence. The drug is safe, not cardiotoxic, does not impair psychomotor or cognitive activity.